Valvular heart disease is changing - a challenge for Africa - David A. Tibbutt, DM, FRCP (Health and Social Sciences Research Institute - South Sudan (HSSRI-SS), 2015)
The pattern of valvular heart disease is changing in Western populations. There are implications for Africa as healthcare improves and people live longer. Over the last half century in Western countries there has been a change in the incidence of valvular heart disease from a rheumatic cause to one of degeneration. Until the age of 64 years all moderate to severe valve disease affects less than 2%. In the group aged 64 - 75 years the proportion increases to 4 - 8% and after age 75 years it rises to 12 - 13%. Mitral incompetence (regurgitation) and aortic stenosis contribute to the majority of cases. Mitral stenosis is much more common in patients who have had rheumatic heart disease. As the population ages the healthcare burden of valvular heart disease will become greater.